Tautomerization Mechanism and Spectral Properties of Porphyrin–Glucose Complexes as Models of Antibacterial Material - Cardenas-Jiron, G; Yanez-Sanchez, M (Springer New York LLC, 2016)
We performed a theoretical study, using density functional theory, about the physical–chemical properties of porphyrin–glucose complexes bonded by a triazine ring (TA) as models of the type photosensitizer-cellulose with potential antibacterial applications. Firstly, we explore the tautomerization mechanism (B3LYP/6-31G(d,p)) in the fragment TA considering three porphyrin–glucose complexes that varies in the porphyrin nature (anionic, cationic, neutral). We characterized the tautomers and the transition states connecting them, and found the keto form [–CONH–] as the most stable tautomer (TA-1). In a second stage, we analyze the ability of the porphyrins as photosensitizers in each porphyrin–glucose complexes in its form TA-1. For the calculation of the UV–Vis spectra, we assessed seven functionals (B3LYP, M05, MPWB1K, PBE, CAM-B3LYP, M06-2X, and LC-BLYP) on a porphyrin, some of which we previously have used. The best agreement with experimental data was obtained at the CPCM(UAKS)-M05/6-31G(d,p) level that then we used to calculate the spectra of the complexes. This functional predicts maximum errors of 0.09 eV for the Q bands. It is showed that the glucose unit does not significantly affect the ability of porphyrin as photosensitizer, and the absorption of Q band of the cationic complex (624 nm) is red shifted with respect to other complexes, which favors its action as photosensitizer. Finally, we focus on the energy released from the fully optimized triplet excited states, which straight relates to the formation of active singlet oxygen. We found that all the porphyrins and their complexes fulfill the requirements to be a good photosensitizer, absorb in the visible light region and release the enough energy to yield the more stable excite state 1Δg for singlet oxygen, which demonstrate that all the systems studied here could be used as antibacterial materials. © 2016, Springer-Verlag Berlin Heidelberg.